APPLICATION OF THE LOGISTIC REGRESSION METHOD TO PREDICT THE RESULTS OF IN VITRO FERTILIZATION - Ismayilova, M.K. (World of Medicine and Biology, 2022)
Development of the predictors of effectivity of treatment of infertility by means of in vitro fertilization is one of the most important tasks of the modern medicine. We have examined 518 patients applying on account of infertility to the Central Clinic of Baku city. All patients were divided into two groups: the patients with onset pregnancy i.e. positive in vitro fertilization intra cytoplasmic sperm injection results – main group (n=234) and patients with negative in vitro fertilization intra cytoplasmic sperm injection efforts – control group (n=284). The criteria precisely differing in the compared groups were chosen among the big quantity of signs at the women with various in vitro fertilization outcomes. These parameters were used at the factor analysis. Basing upon the result of the factor analysis there were assigned the main factors for forecasting the in vitro fertilization outcomes of infertile women by means of logistic regression. The developed model of forecasting the logistic regression allows precisely forecasting the in vitro fertilization outcome upon certain parameters in 86.93 % cases.
Keywords: supplementary reproductive technologies; infertility; logistic regression; predictive value